Integration of "Omics" Strategies for Biomarkers Discovery and for the Elucidation of Molecular Mechanisms Underlying Brugada Syndrome. Issue 6 (20th July 2018) - Scumaci, Domenica; Oliva, Antonio; Concolino, Antonio; Curcio, Antonio; Fiumara, Claudia Vincenza; Tammè, Laura; Campuzano, Oscar; Pascali, Vincenzo L.; Coll, Monica; Iglesias, Anna; Berne, Paola; Casu, Gavino; et al.
Abstract : Purpose: The Brugada syndrome (BrS) is a severe inherited cardiac disorder. Given the high genetic and phenotypic heterogeneity of this disease, three different "omics" approaches are integrated in a synergic way to elucidate the molecular mechanisms underlying the pathophysiology of BrS as well as for identifying reliable diagnostic/prognostic markers. Experimental design: The profiling of plasma Proteome and MiRNome is perfomed in a cohort of Brugada patients that were preliminary subjected to genomic analysis to assess a peculiar gene mutation profile. Results: The integrated analysis of "omics" data unveiled a cooperative activity of mutated genes, deregulated miRNAs and proteins in orchestrating transcriptional and post‐translational events that are critical determining factors for the development of the Brugada pattern. Conclusions and clinical relevance: This study provides the basis to shed light on the specific molecular fingerprints underlying BrS development and to gain further insights on the pathogenesis of this life‐threatening cardiac disease.